Effectiveness of the flipped classroom model in minimizing students’ learning performance gaps in higher education - Gamar Assagaf; Patma Sopamena; Dinar Riaddin; Julham Hukom; Abdulnassir Yassin (DWIJA CENDEKIA: Jurnal Riset Pedagogik, 2024)
Effectiveness of the flipped classroom model in minimizing student achievement gaps in higher education. Various previous experimental studies have highlighted the potential of the flipped classroom model (FCM) for improving student learning performance. However, the question of how far FCM can make a positive contribution to various academic abilities remains unclear. Some studies suggest that some learning models tend to benefit students with higher academic abilities (UA) than those with lower abilities (LA). Objectives: This study aims to explore whether the application of FCM can be effective in reducing the learning performance gap between LA and UA students. Method: We used an ANCOVA test with a 3 x 2 factorial design to answer this research question. We applied three different learning models (FCM, PBL, and Expository) to a total of 25 LA and UA students. Results: The analysis results showed that using the FCM model was more successful in reducing the learning performance gap between LA and UA students compared to the PBL and expository models. Conclusion: These findings make a significant contribution to our understanding of the effectiveness of specific learning models in addressing learning performance gaps, with important implications for the development of more inclusive learning policies and practices.